Effects of various disinfectants on surface roughness and color stability of thermoset and 3D-printed acrylic resin - Farnoush Fotovat; Samaneh Abbasi; Saeed Nikanjam; Behnaz Alafchi; Mandana Baghiat (European Journal of Translational Myology, 2024)
Denture cleansers are extensively utilized to inhibit the colonization of various Candida species. Currently, additive technology in denture fabrication has become more prevalent. This study aims to assess the impact of disinfectants on the surface roughness and color stability of distinct denture bases. Disc-shaped samples (N=66) were exposed to three different disinfectants: 0.5% sodium hypochlorite, 1% hydrogen peroxide, and 2% chlorhexidine. The samples underwent evaluation via spectrophotometry and profilometry, respectively. Data analysis was conducted utilizing analysis of variance (ANOVA) (p < 0.05). Within the heat-cured group, sodium hypochlorite resulted in the most notable change in surface roughness (0.2 μm), while chlorhexidine exhibited the least impact (0.001 μm), showing a significant difference (p <0.008). The color change (ΔE) for 3D-printed samples immersed in all disinfectants was higher compared to heat-cured samples. Among the heat-cured samples, chlorhexidine induced the highest ΔE (2.76), while sodium hypochlorite resulted in the lowest (ΔE = 1.44), and this difference was statistically significant (p <0.008). Chlorhexidine caused the most significant color alteration among the solutions, while sodium hypochlorite induced the most considerable changes in surface roughness.